Economic policy uncertainty and the Indian economy. - Ghosh, Raktim (Emerald points., 2023)
As businesses, consumers, and investors make key financial decisions amid Economic Policy Uncertainty (EPU), there is the danger that many might freeze investment projects and hiring, leading to contractions of the economy. This book examines this and makes important recommendations.